Sharp for SARP: Nonparametric bounds on the behavioural and welfare effects of price changes - Richard Blundell; Martin Browning; Laurens Cherchye; Ian Crawford; Bram De Rock; Frederic Vermeulen (Institute for Fiscal Studies (IFS), 2012)
Sharp nonparametric bounds are derived for Hicksian compensating and equivalent variations. These 'i-bounds' generalize earlier results of Blundell, Browning and Crawford (2008). We show that their e-bounds are sharp under the Weak Axiom of Revealed Preference (WARP). They do not require transitivity. The new i-bounds are sharp under the Strong Axiom of Revealed Preference (SARP). By requiring transitivity they can be used to bound welfare measures. The new bounds on welfare measures are shown to be operationalized through algorithms that are easy to implement.
Keywords: 330